LOS GASTOS ASOCIADOS A INFECCIONES HOSPITALARIAS EN EL CITIO QUIRURJICO Y SU INFLUENCIA EN LOS COSTOS/ EFICIENCIA DE LAS PRESTACIONES HOSPITALARIAS, EN EL HOSPITAL GINECO-OBSTETRIC0S ENRIQUEC. SOTOMAYOR DE LA CIUDAD DE GUAYAQUIL. - Dr. JOSE PABLO CHU LEE (2015)
THE EXPENSES ASSOCIATED WITH HOSPITAL INFECTIONS IN THE SURGICAL CITY AND THEIR INFLUENCE ON THE COSTS/EFFICIENCY OF HOSPITAL PROVISIONS, AT THE ENRIQUEC GINECO-OBSTETRIC HOSPITAL. SOTOMAYOR OF THE CITY OF GUAYAQUIL.